2017
DOI: 10.1002/asi.23970
|View full text |Cite
|
Sign up to set email alerts
|

The mismeasure of science: Citation analysis

Abstract: For several decades we, among others, have criticized the use of citations for evaluative purposes. Although these criticisms have been noted, they have been largely brushed aside or ignored, not addressed head on. This may be for a number of reasons, but we believe the main one is that these criticisms undermine the desire to have an easy "scientific"-that is, quantitative-method of evaluation. Consequently, we continue and update our criticism of the use of citations for evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(49 citation statements)
references
References 73 publications
0
44
0
5
Order By: Relevance
“…Today, citation-based indicators are widely used and play a central role in the evaluation of scientific works. Despite their de facto use as proxies of scientific quality, citations are not able to fully capture the use and influence of scientific papers (Moed, 2005;MacRoberts & MacRoberts, 2017). Bibliometric research has also shown that a variety of factors can influence citation counts (Opthof & Leydesdorff, 2010;Waltman et al, 2011;Larivière & Gingras, 2011).…”
Section: Effect Of Document Characteristics On Citation Impactmentioning
confidence: 99%
“…Today, citation-based indicators are widely used and play a central role in the evaluation of scientific works. Despite their de facto use as proxies of scientific quality, citations are not able to fully capture the use and influence of scientific papers (Moed, 2005;MacRoberts & MacRoberts, 2017). Bibliometric research has also shown that a variety of factors can influence citation counts (Opthof & Leydesdorff, 2010;Waltman et al, 2011;Larivière & Gingras, 2011).…”
Section: Effect Of Document Characteristics On Citation Impactmentioning
confidence: 99%
“…However, weaknesses of citation indexes include that they do not take into account the reasons the article is cited (e.g. as criticism), there may be long delays from publication to placement in citation databases [50], and most importantly, they do not show the impact of the article beyond the academic research community [51,52].…”
Section: Altmetrics and The Importance Of Gaining Public Attentionmentioning
confidence: 99%
“…Despite its frequent use, the method is often criticized. According to Macilwain (2013), a fundamental defect of quantitative research-assessment tools, such as bibliometrics, is that they are "largely built on sand" (p. 255), which means that they cannot directly measure the 'quality of research' and instead use "weak surrogates, such as the citation indices of individuals" (p. 255). An overview of other critical points on bibliometrics (especially citation analysis) can be found in the paper The mismeasure of science: citation analysis, published by Mac-Roberts and MacRoberts (2017).…”
Section: How the Study Of Heuristics Can Inform The Study Of Bibliomementioning
confidence: 99%